2019
DOI: 10.1016/j.cellsig.2019.03.024
|View full text |Cite
|
Sign up to set email alerts
|

The effects of IFITM1 and IFITM3 gene deletion on IFNγ stimulated protein synthesis

Abstract: A B S T R A C TInterferon-induced transmembrane proteins IFITM1 and IFITM3 (IFITM1/3) play a role in both RNA viral restriction and in human cancer progression. Using immunohistochemical staining of FFPE tissue, we identified subgroups of cervical cancer patients where IFITM1/3 protein expression is inversely related to metastasis. Guide RNA-CAS9 methods were used to develop an isogenic IFITM1/IFITM3 double null cervical cancer model in order to define dominant pathways triggered by presence or absence of IFIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 74 publications
(108 reference statements)
10
47
0
Order By: Relevance
“…To filter out target peptide spectrum matches over the decoy-peptide spectrum matches, a fixed FDR of 1% was set at the peptide level. Mass recalibration and label-free quantification (LFQ) of area under the curve MS1 peaks were carried out using Proteome Discoverer nodes, Spectrum Files RC, Minora Feature Detector, and Feature Mapper ( 31 , 32 , 33 , 34 , 35 , 36 , 37 ). Minora Feature Detector is the dominant algorithm behind the LFQ whereby it first detects chromatographic peaks in the raw spectral data and maps them to identified peptide spectrum matches.…”
Section: Methodsmentioning
confidence: 99%
“…To filter out target peptide spectrum matches over the decoy-peptide spectrum matches, a fixed FDR of 1% was set at the peptide level. Mass recalibration and label-free quantification (LFQ) of area under the curve MS1 peaks were carried out using Proteome Discoverer nodes, Spectrum Files RC, Minora Feature Detector, and Feature Mapper ( 31 , 32 , 33 , 34 , 35 , 36 , 37 ). Minora Feature Detector is the dominant algorithm behind the LFQ whereby it first detects chromatographic peaks in the raw spectral data and maps them to identified peptide spectrum matches.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study reported that both IRF1 and IFI6 are positively associated with the drug-specific chemosensitivity of gastric cancer ( 56 ). Gómez-Herranz et al ( 57 ) revealed that IRF1 is one of the most dominant IFN-γ inducible proteins whose synthesis is attenuated in IFITM1/IFITM3-negative cervical cancer cells. Yang et al ( 58 ) reported that IRF1 could directly bind to one site of the IFI35 promoter and mediate IFN-γ-dependent transcriptional activation of IFI35 in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IFITMs are involved in various cellular processes, which has both direct and indirect effects on immunity ( 58 ). A recent study showed that the expression levels of IRF1, human leucocyte antigen (HLA)-B, and ISG15 protein were attenuated in the IFITM1/IFITM3 double-null cells ( 59 ). Consistently, the ectopic expression of EcIFITM1 significantly increased the levels of IRF7, ISG15, and MXI mRNA, while knockdown of EcIFITM1 displayed an opposite effect.…”
Section: Discussionmentioning
confidence: 99%